Σχεδιασμός Ανθρωποκίνητου μικρού οχήματος/οργάνου εκγύμνασης του αάνω μέρους του σώματος - Κωνσταντίνου, Ανδρούλα; Ναθαναήλ, Κωνσταντίνος; Στυλιανού, Θεόδωρος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικών Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2019)
The objective of this diploma thesis is to design a small human-powered vehicle, which will also provide training of the upper-body. The term «human-powered», pertains to the feet that the movement of the vehicle is derived exclusively via human power, without any other external sources of energy. To achieve this objective, existing vehicles with similar function as well as pertinent upper body exercise equipment were studied. Then, following the development of the ideas that emerged, it was decided to design a four-wheel vehicle that combines cycling with rowing. Cycling and rowing are fueling the vehicle's movement and at the same time constitute the means for training, while driving. Furthermore, a fitness beam is attached to the vehicle and offers the ability to work out the upper body when the vehicle is stationary. Throughout design, the design team has implemented a continuous optimization of the vehicle’s parts with the help of SolidWorks® software, until the desired results were achieved. Ultimately, the human-powered vehicle that has been designed and optimized meets all the imposed requirements.
Keywords: human-powered; quadricycle; tricycle; upper body exercise; hand and foot cycle; rowing cycle